Auditoría financiera y su relación con los resultados económicos de la compañía bananera latinoamericana banalati S. A., cantón la Maná, periodo 2012. - Baraja Mena, Martha Roció (2014)
This research aims to determine the relationship of the reasonableness of the financial statements and the economic performance of Latin American Banana Company BANALATI SA , Canton La Maná , 2012 period , in order to suggest the completion of a financial audit to its development assess the level of confidence efficiency and compliance presenting institution. For the audit process four files Standing Archive , Archive Planning, Analysis and Archive the audit report , each with the relevant information required for each situation and concludes with the issuance of the development in the respective reports are taken into account this process the non-experimental design and exploratory research was used because it is considered that the issue is under-researched and therefore is required to search for information on primary and secondary sources and the descriptive model is used because it facilitated know in detail the financial characteristics of the company , in the same way helped to credits involved processes also allowed to assess important variables related to determine the accuracy of financial information is the back with the ifrs for smes. conclusion of the investigation can be established importance of conducting a financial audit that allowed us to corroborate the financial information provided by the company is reliable. As well having a high level of efficiency in the use of economic resources.